Peace as process : reconciliation and conflict resolution in South Asia - Samāddāra, Raṇabīra; Reifeld, Helmut; Konrad-Adenauer-Stiftung. (New Delhi : Manohar Publishers & Distributors, 2001)
Contributed workshop papers.
"Konrad Adenauer Foundation."
Includes bibliographical references and index.
BIED
Complimentary copy from BIED
Keywords: Peace -- South Asia -- Congresses; Conflict management -- South Asia -- Congresses